The effect of JuanBiQiangGu granules in combination with methotrexate on joint inflammation in rheumatoid arthritis: a randomized controlled trial - Ran, Lei; Xu, Bo; Han, Hai-Hui; Wang, Jian-Ye; A, Xin-Yu; Cao, Bo-Ran; Meng, Xiao-Hui; Zhang, Cheng-Bo; Xin, Peng-Fei; Qiu, Guo-Wei; Xiang, Zheng; Pei, Shao-Qiang; et al. (Frontiers in Pharmacology, 2023)
Background: Rheumatoid arthritis (RA) joint inflammation severely affects joint function and quality of life in patients and leads to joint deformities and limb disability. The non-steroidal anti-inflammatory drugs used in the treatment of RA do not fully control the progression of joint inflammation and bone destruction and have notable adverse reactions. Traditional Chinese medicine formula JuanBiQiangGu Granules (JBQG) are commonly used for the treatment of RA inflammation and delay of bone destruction, but has not been evaluated through high-quality clinical studies. There is a pressing need for well-designed, randomized, parallel, controlled clinical studies to evaluate the exact effect of JBQG on RA joint inflammation and improvement of patient quality of life. Methods: This is a randomized, parallel, controlled clinical study in which 144 patients with rheumatoid arthritis who met the inclusion criteria were randomly assigned to 2 groups in a 1:1 ratio. The JBQG group received methotrexate 7.5 mg qw and JBQG granules 8 mg tid, while the MTX group received methotrexate 7.5 mg qw. The endpoint was 12 weeks after treatment. Relevant indices at baseline, 4 weeks, 8 weeks, and 12 weeks after treatment were observed and recorded, and DAS28-ESR, HAQ-DI, and Sharp scores were recorded for each patient. Blood samples were collected to test for CRP, ESR, TNF-α, IL-1β, IL-6, IL-17, and INF-γ, and adverse reactions and liver and kidney function (AST, ALT, Cr, BUN) were recorded for safety assessment. After 12 weeks of treatment, the effect of JBQG granules on disease activity, improvement in bone damage, and patient quality of life scores and safety in RA patients were evaluated. Results: A total of 144 subjects completed treatment (71 in the JBQG group and 73 in the MTX group) and were included in the analysis. At baseline, there were no significant differences between the groups in terms of the observed indicators (p > 0.05). After treatment, 76.06% of patients in the JBQG group had DAS28-ESR levels below or equal to Low, including 45.07% in Remission and 5.63% in High, compared to 53.1% in the MTX group below or equal to Low, 12.33% in Remission, and 17.81% in High. CRP was significantly reduced (8.54 ± 5.87 vs. 11.86 ± 7.92, p < 0.05, p = 0.005), ESR was significantly reduced (15.1 ± 6.11 vs. 21.96 ± 9.19, p < 0.0001), TNF-α was significantly reduced (1.44 ± 0.83 vs. 1.85 ± 1.07, p < 0.05, p = 0.011), IL-17 was significantly reduced (0.53 ± 0.33 vs. 0.71 ± 0.38, p < 0.05, p = 0.004), and INF-γ was significantly reduced (3.2 ± 1.51 vs. 3.89 ± 1.77, p < 0.05, p = 0.014). The median (IQR) OPG in the JBQG group was 2.54 (2.21–3.01), significantly higher than in the MTX group 2.06 (1.81–2.32), p < 0.0001), and the median (IQR) β-CTX in the JBQG group was 0.4 (0.32–0.43), significantly lower than in the MTX group 0.55 (0.47–0.67), p < 0.0001). The median (IQR) VSA scores were 2 (1–3), a decrease from 3 (2–4) in the MTX group (p < 0.0001). The median (IQR) Sharp scores were 1 (1–2), a decrease from 2 (1–2) in the MTX group, but the difference was not statistically significant (p > 0.05, p = 0.28). The median (IQR) HAQ-DI scores were 11 (8–16), significantly lower than in the MTX group 26 (16–30) (p < 0.0001). The median (IQR) AST in the JBQG group was 16 (12–20), with a significant difference compared to the MTX group 19 (13–25) (p < 0.01, p = 0.004); the median (IQR) ALT in the JBQG group was 14 (10–18), with a significant difference compared to the MTX group 16 (11–22.5) (p < 0.05, p = 0.015). There were no statistically significant differences in Cr or BUN (p > 0.05). Conclusion: JuanBiQiangGu Granules can be used to treat patients with rheumatoid arthritis, alleviate joint inflammation, reduce the incidence of adverse reactions to methotrexate, and has good safety. Clinical Trial Registration:http://www.chinadrugtrials.org.cn/index.html; identifier: ChiCTR2100046373.